2009
DOI: 10.1016/j.ijid.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Study on invasive fungal infections in immunocompromised patients to present a suitable early diagnostic procedure

Abstract: It may be concluded that the molecular assay would help in the diagnosis of invasive fungal infections at the early stage of infection, before clinical manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In the present study, three patients had Aspergillus DNA in their blood samples prior to transplantation with no clinical criteria; only one patient survived. Other studies reported that molecular methods can help detect the fungal infections before clinical findings [23,24]. Our data show that fungal DNA can be identified prior to clinical manifestations in patients with hematological disorders, who received multiple chemotherapy and steroid treatments, and who were neutropenic at different stages of their sicknesses.…”
Section: Discussionmentioning
confidence: 57%
“…In the present study, three patients had Aspergillus DNA in their blood samples prior to transplantation with no clinical criteria; only one patient survived. Other studies reported that molecular methods can help detect the fungal infections before clinical findings [23,24]. Our data show that fungal DNA can be identified prior to clinical manifestations in patients with hematological disorders, who received multiple chemotherapy and steroid treatments, and who were neutropenic at different stages of their sicknesses.…”
Section: Discussionmentioning
confidence: 57%
“…In such cases, PCR facilitates species identification, which cannot be achieved through microscopy but can serve an important role in guiding antifungal therapy. Multiplex PCR has also been tested as a method to detect fungal species in whole-blood (236,238,(243)(244)(245), serum (246), or BAL fluid (247) samples from patients at high risk for IFIs. The results are variable, but most studies report superior sensitivities and specificities of Ͼ80% (236,238,243,248).…”
Section: Pcrmentioning
confidence: 99%
“…Badiee New methods for the identification of fungi, although still not widely available, include immunofluorescence staining, electron microscopy and polymerase chain reaction (PCR). The potential utility of PCR-based techniques for improving the diagnosis of infections is well recognized, and the use of PCR for this purpose is expanding [7][8][9][10][11] . PCR assays targeting Candida , Aspergillus and Fusarium have been tested preliminarily in vitreous specimens [8,9] .…”
Section: Introductionmentioning
confidence: 99%